Application of complexes of bath-houses procedures in practice of work of sporting masseur - Підкопай [Pidkopay D.] Денис Олегович; Підкопай [Pidkopay D.] Т. В. (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]–> The developed and tested special complexes of hidro-bath procedures are resulted. Application of bath-houses procedures and bath-house sporting massage in a complex rotined the expressed and forecast effect, and methods were inculcated in the training process of short-trackers different qualification in the stages of annual preparation. information of research work is described with short-trackers – by the sportsmen of different qualification. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>